KAJIAN KETIMPANGAN WILAYAH DI KAWASAN SUBOSUKAWONOSRATEN TAHUN 2001-2016 - Yetti Anita Sari; Sri Rum Giyarsih; Evita Hanie Pangaribowo (Universitas Gadjah Mada, 2018)
Regional disparity was a common problem in developing countries. Different regional potentials result in disparity between regions. This study aims to analyze regional disparity in Subosukwonosraten region during 2001-2016 and to determine factors that affect regional disparity in Subosukawonosraten. Analysis techniques used in this study were entropy theil index and panel data regression. The result showed that regional disparity in Subosukawonosraten tends to increase during 2001-2016. Showed by the results of the total theil index in 2001 was 8.8133 to 12.4879 in 2016. The results of panel data regression fixed effect with Weighted Least Squares were share indsutry sector and share agriculture sector have the negative and significant impact on regional disparity. Enrollment rate, morbidity, and population growth have the positive and significant impact on regional disparity.